Ekspresi dan Pathway Analisis Gen CD14 dan IL10 pada Sapi Perah yang Terinfeksi Mastitis Subklinis (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2019)
Mastitis is an inflammation of  internal udder tissue caused by bacteria, it decrease milk production both in quality and quantity. This study was aimed to identify expression and pathway analysis of gene CD14 and IL10 as resistance genes in dairy infected with subclinical mastitis. Sample were taken from milk and blood 10 healthy dairy and 10 dairy containing subclinical mastitis used for CMT and RNA isolation used for gene expression analysis. The result showed that expression in healthy dairy CD14 gene had a higher expression (P